Oxidative stress on cardiotoxicity after treatment with single and multiple doses of doxorubicin - Pacifico de Freitas Segredo, M. [UNESP]; Favero Salvadori, D. M. [UNESP]; Rocha, Noeme Sousa [UNESP]; Fontes Moretto, F. C. [UNESP]; Correa, C. R. [UNESP]; Camargo, E. A. [UNESP]; Almeida, D. C. de [UNESP]; Silva Reis, R. A. [UNESP]; Murbach Freire, C. M. [UNESP]; Braz, M. G. [UNESP]; Tang, G.; Matsubara, L. S. [UNESP]; et al. (Sage Publications Ltd, 2014)
The mechanism of doxorubicin (DOX)-induced cardiotoxicity remains controversial. Wistar rats (n = 66) received DOX injections intraperitoneally and were randomly assigned to 2 experimental protocols: (1) rats were killed before (-24 h, n = 8) and 24 h after (+24 h, n = 8) a single dose of DOX (4 mg/kg body weight) to determine the DOX acute effect and (2) rats (n = 58) received 4 injections of DOX (4 mg/kg body weight/week) and were killed before the first injection (M-0) and 1 week after each injection (M-1, M-2, M-3, and M4()) to determine the chronological effects. Animals used at M-0 (n = 8) were also used at moment -24 h of acute study. Cardiac total antioxidant performance (TAP), DNA damage, and morphology analyses were carried out at each time point. Single dose of DOX was associated with increased cardiac disarrangement, necrosis, and DNA damage (strand breaks (SBs) and oxidized pyrimidines) and decreased TAP. The chronological study showed an effect of a cumulative dose on body weight (R = -0.99, p = 0.011), necrosis (R = 1.00, p = 0.004), TAP (R = 0.95, p = 0.049), and DNA SBs (R = -0.95, p = 0.049). DNA SBs damage was negatively associated with TAP (R = -0.98, p = 0.018), and necrosis (R = -0.97, p = 0.027). Our results suggest that oxidative damage is associated with acute cardiotoxicity induced by a single dose of DOX only. Increased resistance to the oxidative stress is plausible for the multiple dose of DOX. Thus, different mechanisms may be involved in acute toxicity versus chronic toxicity.
Keywords: Doxorubicin; heart; rat; antioxidant capacity; DNA damage; morphology